1998
DOI: 10.1056/nejm199810223391703
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Year Follow-up Study of Ventilatory Function in Adults with Asthma

Abstract: In a sample of the general population, people who identified themselves as having asthma had substantially greater declines in FEV1 over time than those who did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
759
11
29

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,127 publications
(830 citation statements)
references
References 29 publications
31
759
11
29
Order By: Relevance
“…Overall, these observations would suggest that higher levels of copper in the blood are likely to contribute to the neutrophilic inflammation involved in the pathogenesis of COPD in humans (Barnes, 2000), rather than result from it (Boosalis et al, 1996). Alternatively, as high levels of serum copper have also been reported in asthma (Malvy et al, 1993;Kadrabova et al, 1996;Vural et al, 2000), in light of the studies cited above (Boosalis et al, 1996;Kennedy et al, 1998;Rice et al, 2001), it is also possible that increased plasma copper contributes to the accelerated decline in lung function observed in those with asthma (Lange et al, 1998).…”
Section: Coppermentioning
confidence: 88%
“…Overall, these observations would suggest that higher levels of copper in the blood are likely to contribute to the neutrophilic inflammation involved in the pathogenesis of COPD in humans (Barnes, 2000), rather than result from it (Boosalis et al, 1996). Alternatively, as high levels of serum copper have also been reported in asthma (Malvy et al, 1993;Kadrabova et al, 1996;Vural et al, 2000), in light of the studies cited above (Boosalis et al, 1996;Kennedy et al, 1998;Rice et al, 2001), it is also possible that increased plasma copper contributes to the accelerated decline in lung function observed in those with asthma (Lange et al, 1998).…”
Section: Coppermentioning
confidence: 88%
“…Analyses using pre-BD values showed larger decline per year, but did not influence on the role of the other determinants in the multivariate analyses. Previous studies have suggested accelerated lung function declines in asthma [28,29] and in a review of adult-onset asthma decline in FEV₁ varied between 25 and 95 ml per year [6]. Still, recent studies have found decline in FEV₁ in asthmatics of 25.3 [18] and 25.6 ml [30] per year, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not correct for the natural history of chronic obstructive pulmonary disease [26,27] that would also explain increasing dyspnoea with time, in which radiation-induced lung damage could obviously also play a role.…”
Section: Discussionmentioning
confidence: 99%